(untitled) (IASH Indian Journal of Arid Horticulture, 2026)
During the experimentation studied the effect of five planting time and three varieties of tomato during winter season of 2019-2020, 2020-21 and 2021-22. During the experiment three tomato variety viz. WS-1299 (V1 ), Krishna (V2 ) and Bavandar (V3 ) were studied with five different dates of planting viz. 30 December (D1 ), 15 December (D2 ), 15 January (D3 ), 30 January (D4 ) and 15 February (D5 ). In which the yield of tomato was significantly affected by different sowing dates and verities. Among varieties and planting dates the variety Bavander (V3 ) planted on 15 January (D3 ) produced significantly higher number of fruits/ plant (39.70), fruit weight (83.25 g) and fruit yield (727.20 q/ ha) with the maximum B:C ratio (4.05).